Effect of nanoclay contents on properties, of bagasse flour/reprocessed high density polyethylene/nanoclay composites - Samariha, Ahmad; Hooman Hemmasi, Amir; Ghasemi, Ismail; Bazyar, Behzad; Nemati, Mohammad (Maderas. Ciencia y Tecnología, 2025)
The effect of nanoclay contents on the physical and mechanical properties of bagasse flour/ reprocessed high density polyethylene (rHDPE)/ nanoclay composites was investigated. The bagasse flour content was constant at 50%, the maleic anhydride content was constant at 3%, and the nanoclay (Cloisite 30B) content was set at three different levels: 0%, 2%, and 4%. The materials were mixed in a co-rotating twin-screw extruder; afterwards, the specimens were fabricated using an injection molding method. The water absorption and mechanical properties, such as flexural and tensile strength, flexural and tensile modulus, and notched impact strength, were measured. The nanoclay dispersion was examined by X-ray diffraction. The results indicated that tensile and flexural modulus increased with an increase in nanoclay content. Also By increasing the nanoclay content at 2 wt.%, the tensile and flexural strengths of the composite were increased. However, the addition of 4 wt.% nanoclay resulted in reductions of these properties. Water absorption decreased with increasing nanoclay content. The structural examination of the bagasse polymer composite with X-ray diffraction showed that the nanoclay was distributed as an intercalated structure in the polymer matrix, and the d-spacing of layers decreased with increasing nanoclay content. Scanning electron microscopy (SEM) showed that 2% nanoclay samples with lower and more uniform pores compared at 4% nanoclay samples, respectively.